Polskie międzywojenne czasopisma do nauki języka angielskiego - wstęp do charakterystyki genologicznej = Polish interwar periodicals for learning English - introduction to genological characteristics - Kotlarska, Irmina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the study is a genologically oriented review of interwar periodicals promoting knowledge of the English language among Poles. Three monthly magazines and one biweekly document the intensive development of the press and the growing position of English among Poles in that period. The article uses the way of understanding the genre and the tools for its description proposed by Maria Wojtak. The periodicals discussed represent specialized press.
Keywords: genologia lingwistyczna; prasa neofilologiczna; dwudziestolecie międzywojenne; popularyzacja znajomości języka angielskiego; linguistic genealogy; neophilological press; interwar period; popularisation of English language